A new species of Micromaldane (Polychaeta: Maldanidae) from the Falkland Islands, southwestern Atlantic, with notes on reproduction - Darbyshire, Teresa (Zootaxa, 2013)
Micromaldane shackletoni n. sp. is described from the Falkland Islands in the southwest Atlantic. It is only the eighth species of Micromaldane to be recognized worldwide and is a new record of the genus for the Falkland Islands. The main characters of the new species are: up to 23 chaetigerous segments; nuchal organs as rounded ciliated pits with small central grooves anteriorly; two kinds of notochaetae: lancet-shaped chaetae and fine capillaries; neurochaetae as a single row of strongly curved, avicular uncini; a single pre-anal achaetigerous segment and anal plaque funnel-shaped with a crenated edge. This new species is a simultaneous hermaphrodite, only the second report of this reproductive mode in the genus along with Micromaldane androgyne Rouse, 1990. The stages of larval development from internal gametes to external in-tube development are also discussed.